Developing a Bilingual Company Profile as Promotional Media and E-Catalogue for Agro Mineral Water - Tawang Zoradiva; Hilda Dwi Cahyani (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study addresses the lack of effective, informative, and accessible promotional media at Agro Group, a company operating in the bottled drinking water industry. The absence of a structured company profile, product catalog, and digital promotional tools limited the company’s ability to communicate its brand identity, product variants, and credibility to both domestic and international stakeholders. This research applied the Design and Development Research (DDR) method, consisting of four stages: preliminary study, design, development, and evaluation. Data were collected through observation, interviews, documentation, expert validation, and field testing. The outcome of this study is a bilingual (Indonesian–English) flipbook that integrates comprehensive company information, including background, product variants and packaging sizes, certifications, sustainability initiatives, and an interactive feature linking to a 2-minute 19-second bilingual company profile video. The validation and field testing results yielded an average score of 4.53 out of 5 (90.6%), indicating that the developed product is effective and professionally acceptable. This bilingual flipbook enhances Agro Mineral Water’s promotional strategy by improving credibility, accessibility, and engagement with both local and global audiences.